Serotonergic modulation in neuropathy induced by oxaliplatin: Effect on the 5HT(2C) receptor - Baptista-de-Souza, Daniela [UNESP]; Mannelli, Lorenzo Di Cesare; Zanardelli, Matteo; Micheli, Laura; Nunes-de-Souza, Ricardo Luiz [UNESP]; Canto-de-Souza, Azair [UNESP]; Ghelardini, Carla (Elsevier B.V., 2014)
Fluoxetine has been shown to be effective in clinical and experimental studies of neuropathic pain. Besides to increase serotonin levels in the synaptic cleft, fluoxetine is able to block the serotonergic 5-HT2C receptor subtype, which in turn has been involved in the modulation of neuropathic pain. This study investigated the effect of repeated treatments with fluoxetine on the neuropathic nociceptive response induced by oxaliplatin and the effects of both treatments on 5-HT2C receptor mRNA expression and protein levels in the rat spinal cord (SC), rostral ventral medulla (RVM), midbrain periaqueductal gray (PAG) and amygdala (Amy). Nociception was assessed by paw-pressure, cold plate and Von Frey tests. Fluoxetine prevented mechanical hypersensitivity and pain threshold alterations induced by oxaliplatin but did not prevent the impairment in weight gain induced by this anticancer drug. Ex vivo analysis revealed that oxaliplatin increased the 5-HT2C receptor mRNA expression and protein levels in the SC and PAG. Similar effects were observed in fluoxetine-treated animals but only within the PAG. While oxaliplatin decreased the 5-HT2C mRNA expression levels in the Amy, fluoxetine increased their protein levels in this area. Fluoxetine impaired the oxaliplatin effects on the 5-HT2C receptor mRNA expression in the SC and Amy and protein levels in the SC. All treatments increased of 5-HT2C receptor mRNA expression and protein levels in the PAG. These results suggest that the effects of fluoxetine on neuropathic pain induced by oxaliplatin are associated with quantitative changes in the 5-HT2C receptors located within important areas of the nociceptive system. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Oxaliplatin; Fluoxetine; Periaqueductal gray matter (PAG); Spinal cord; Amygdala; 5-HT2C receptors